A New Route for Fabricating On‐Chip Chalcogenide Microcavity Resonator Arrays. Issue 7 (6th May 2014) - Aktas, Ozan; Ozgur, Erol; Tobail, Osama; Kanik, Mehmet; Huseyinoglu, Ersin; Bayindir, Mehmet
<x xml:space="preserve">Abstract</x> High‐yield production and on‐chip integration of high‐Q chalcogenide microresonators with various sizes and geometrical shapes (spherical, spheroidal, and ellipsoidal) and with sub‐nanometer surface roughness is achieved. The high‐throughput and low‐cost production of chalcogenide spherical microresonators works via inducing a Plateau‐Rayleigh instability within a multimaterial fiber in extended lengths. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>